When Favoritism Becomes a Crime: A Comparative Analysis of Nepotism in Anti-Corruption Enforcement - Priyambodo, Muhammad Bagus; Wahyudi, Slamet Tri (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Nepotism, as a form of favoritism, continues to pose a significant threat to public sector integrity, particularly in Indonesia where familial ties often influence appointments and resource allocation. This study aims to critically analyze the legal treatment of nepotism in Indonesia under Act No. 28 of 1999 and compare it with Australia’s approach through the common law and statutory offence of Misconduct in Public Office (MIPO). Using a normative legal research method, the study examines statutory texts, judicial precedents, and institutional practices in both countries. It highlights significant legal and institutional shortcomings in Indonesia’s framework, including vague definitions of key terms, lack of enforcement mechanisms, and the exclusion of nepotism cases from the jurisdiction of the Corruption Eradication Commission (KPK). The novelty of this research lies in its comparative analysis, extending beyond domestic critique by systematically contrasting Indonesia’s narrow and fragmented legal approach with Australia’s broader, enforceable, and institutionally supported anti-nepotism framework. The findings reveal that while Indonesia limits nepotism to material harm in public appointments and procurement, Australia criminalizes a wider range of misconduct through clearly defined laws enforced by independent anti-corruption commissions. This contrast underscores the need for Indonesia to reform its legal definitions, expand enforcement authority, and integrate anti-nepotism measures with broader governance reforms. The study concludes that strengthening Indonesia’s legal and institutional capacity, informed by Australia’s model, is essential to addressing nepotism as both a legal and governance challenge.